Chiral conducting polymer nanomaterials: synthesis and applications in enantioselective recognition - Zhou, Chuanqiang; Sun, Xiaohuan; Han, Jie (Materials chemistry frontiers, 2020)
Chiral conducting polymer (CCP) nanomaterials have been the subject of several studies due to their unique electrical and chiroptical properties as well as promising applications. This review mainly summarizes the advances made in the synthesis and applications of CCP nanomaterials in the past two decades. According to the origin of chirality, the fabrication of CCP nanomaterials can be distinguished into chiral induction and achiral preparation strategies. Under the induction of chiral factors (such as chiral substituent, chiral doping acid, or chiral template), the chirality of the conducting polymer (CP) nanomaterials is induced by the chirality transfer from the chiral factors to the CP nanomaterials. In achiral preparation systems, the asymmetrical assembly of CPs results in the supramolecular chirality of the CP nanomaterials. Subsequently, the applications of CCP nanomaterials in enantioselective recognition are reviewed. Besides, the challenges and prospects for constructing advanced CCP nanomaterials are discussed. Recent progress made in the synthesis, mechanism, and applications involving the enantioselective separation and sensing of chiral conducting polymer nanomaterials has been reviewed.